Remarks at Session 2 of the G20 Finance Ministers and Central Bank Governors Meeting, February 26, 2021 - Malpass, David (World Bank, Washington, DC, 2021)
World Bank Group President David Malpass spoke about the need to foster financial inclusion, and to support digital systems that allow high transaction volumes at very low cost. He mentioned that the high costs for cross-border payments hamper economic development and cause payments to flow underground. Working with global partners, the World Bank is leading efforts to increase efficiency, transparency, and competition in the market for remittances worldwide. Developing countries face key challenges related to domestic debt, non-performing loans (NPLs), and bankruptcy processes. He urged that diverse input should be voiced on international environmental taxation, on the increased financial regulation related to climate change, and on stable coins.